2022
DOI: 10.1002/mlf2.12033
|View full text |Cite
|
Sign up to set email alerts
|

A novel Methylomirabilota methanotroph potentially couples methane oxidation to iodate reduction

Abstract: Impact statement Methane oxidizing microbes play a key role in reducing the emission of this potent greenhouse gas to the atmosphere. The known versatility of the recently discovered anaerobic Methylomirabilota methanotrophs is limited. Here, we report a novel uncultured Methylomirabilis species, Candidatus Methylomirabilis iodofontis, with the genetic potential of iodate respiration from biofilm in iodine‐rich cavern spring water. Star‐like cells resembling Methylomirabilis oxyfera were directly observed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…However no dissimilatory iodate-reducing MAG was retrieved by binning from our groundwater metagenomes. This is probably attributable to the relatively lower abundance of idrA , as compared to that for other C-, N-, and S-metabolizing genes . A similar phenomenon was also observed by the absence of dissimilatory arsenate-reducing MAGs in those arrA -containing metagenomes from As-contaminated groundwater .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However no dissimilatory iodate-reducing MAG was retrieved by binning from our groundwater metagenomes. This is probably attributable to the relatively lower abundance of idrA , as compared to that for other C-, N-, and S-metabolizing genes . A similar phenomenon was also observed by the absence of dissimilatory arsenate-reducing MAGs in those arrA -containing metagenomes from As-contaminated groundwater .…”
Section: Discussionsupporting
confidence: 72%
“…This is probably attributable to the relatively lower abundance of idrA, as compared to that for other C-, N-, and S-metabolizing genes. 45 A similar phenomenon was also observed by the absence of dissimilatory arsenate-reducing MAGs in those arrA-containing metagenomes from Ascontaminated groundwater. 46 Given the sporadic presence of putative idrA gene in global groundwater metagenomes (e.g., Utah and Colorado, USA and Horonobe, Japan), our results suggest that similar to the iodine-rich marine environment, dissimilatory iodate-reducing bacteria may play a key role in the production of iodide in geogenic high iodine groundwater.…”
Section: Discussionmentioning
confidence: 65%
“…S4). Interestingly, this included several representatives of uncultured candidate taxa (e.g., Rokubacteriales , Binatota ) thought to be important in lithotrophic and methylotrophic nutrient cycling processes as well as alkane degradation ( 29 , 39 , 40 ), which may reflect selection by organic contaminants that tend to be deposited along with heavy metals by coal-burning industries. These uncultured taxa have only recently been named, but at least one study has shown enrichment of Rokubacteriales at a heavy metal mining site ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than five Candidatus species for the n-DAMO process having been reported to date (e.g., “ Candidatus Methylomirabilis oxyfera”,Candidatus Methylomirabilis sinica”,Candidatus Methylomirabilis lanthanidiphila”, “ Candidatus Methylomirabilis limnetica” and “ Candidatus Methylomirabilis iodofontis”). “ Ca.…”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, the n-DAMO process has attracted much attention recently as a promising clean bioprocess for denitrification in sewage treatment due to significant energy saving and GHG reduction. 13 More than five Candidatus species for the n-DAMO process having been reported to date (e.g., "Candidatus Methylomirabilis oxyfera", 7 "Candidatus Methylomirabilis sinica", 14 " Candidatus Methylomirabilis lanthanidiphila", 15 "Candidatus Methylomirabilis limnetica" 16 and "Candidatus Methylomirabilis iodofontis" 17 ). "Ca.…”
Section: Introductionmentioning
confidence: 99%